Crush and removal of biliary stones by peroral direct cholangioscopy and W‐shaped grasping forceps after hepaticojejunostomy. Issue 7 (5th October 2020) - Hasegawa, Naoyuki; Endo, Masato; Terasaki, Masahiko
Abstract : Watch a video of this article